2020
DOI: 10.3390/cryst10080663
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Neural Networks in Crystal Growth of Electronic and Opto-Electronic Materials

Abstract: In this review, we summarize the results concerning the application of artificial neural networks (ANNs) in the crystal growth of electronic and opto-electronic materials. The main reason for using ANNs is to detect the patterns and relationships in non-linear static and dynamic data sets which are common in crystal growth processes, all in a real time. The fast forecasting is particularly important for the process control, since common numerical simulations are slow and in situ measurements of key process par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…ANNs architectures (or topologies) are versatile and can be built for clustering, classification, regression, or dimensionality reduction . ANNs are prone to overfit data due to their high number of parameters.…”
Section: Overview Of Machine Learning Algorithms and Techniquesmentioning
confidence: 99%
“…ANNs architectures (or topologies) are versatile and can be built for clustering, classification, regression, or dimensionality reduction . ANNs are prone to overfit data due to their high number of parameters.…”
Section: Overview Of Machine Learning Algorithms and Techniquesmentioning
confidence: 99%
“…The Euclidean distance of the intensity difference between each peak of the obtained XRD was used for reference, and the XRD for the experiment was calculated. The Euclidean distance dIJref,exp) between the literature values and experimental values is expressed as formula (1).…”
Section: Data Set Preparationmentioning
confidence: 99%
“…There have been several reports on the use of machine learning in crystal growth research. 1 Tsunooka et al succeeded in rapidly predicting the convection in a melt using machine learning. 2 Boucetta et al showed that the measurement of the location around the reaction vessel in the furnace, that is, the region with a high-temperature thermal gradient, is important for predicting the thermal distribution in the furnace.…”
Section: Introductionmentioning
confidence: 99%
“…Besides validating heating profiles, many detailed validations for the ingot properties are essential for this integrated framework. 26 …”
Section: Introductionmentioning
confidence: 99%